Decision Support System for Minahasa Cultural Preservation Priorities Using SAW TOPSIS: Sistem Pendukung Keputusan Prioritas Pelestarian Budaya Minahasa Berbasis SAW dan TOPSIS - Anthone, Fajriyan; kenap, Audy Aldrin; Usoh, Elni Jeini (Universitas Muhammadiyah Sidoarjo, 2026)
General Background The rapid development of digital technology requires structured systems to support sustainable cultural heritage preservation through data-driven approaches. Specific Background In Minahasa, cultural assets such as ceremonies and traditional clothing face challenges due to limited analytical systems for prioritization, as existing platforms mostly function as static repositories. Knowledge Gap Previous studies rarely integrate multiple Multi-Criteria Decision Making methods simultaneously in cultural preservation contexts, and cross-validation between SAW and TOPSIS remains limited. Aims This study aims to design and implement a web-based Decision Support System to determine preservation priorities of Minahasa cultural heritage using SAW and TOPSIS methods. Results The system, developed using the waterfall model and validated through testing, shows consistent ranking results, with the Waruga Traditional Funeral Ceremony identified as the highest priority, followed by Kabasaran Traditional Clothing, while minor variations appear in mid-ranked alternatives. Novelty The study introduces a comparative integration of SAW and TOPSIS within a web-based system to evaluate ranking consistency and sensitivity in cultural heritage decision-making. Implications The findings provide a quantitative and transparent model that supports objective policy formulation and promotes sustainable, data-driven cultural preservation strategies for local governments. Highlights• Consistent ranking results across dual multi-criteria algorithms• Waruga ceremony identified as highest preservation priority• Web-based system supports transparent policy formulation KeywordsDecision Support System; Cultural Heritage; Minahasa; SAW Method; TOPSIS Method